Characterization of the Jet-Flow Overpressure Model of Traumatic Brain Injury in Mice - Min-Kyoo Shin; Edwin V?zquez-Rosa; Coral J. Cintr?n-P?rez; William A. Riegel; Matthew M. Harper; David Ritzel; Andrew A. Pieper (Neurotrauma Reports, 2021)
The jet-flow overpressure chamber (OPC) has been previously reported as a model of blast-mediated traumatic brain injury (bTBI). However, rigorous characterization of the features of this injury apparatus shows that it fails to recapitulate exposure to an isolated blast wave. Through combined experimental and computational modeling analysis of gas-dynamic flow conditions, we show here that the jet-flow OPC produces a collimated high-speed jet flow with extreme dynamic pressure that delivers a severe compressive impulse. Variable rupture dynamics of the diaphragm through which the jet flow originates also generate a weak and infrequent shock front. In addition, there is a component of acceleration-deceleration injury to the head as it is agitated in the headrest. Although not a faithful model of free-field blast exposure, the jet-flow OPC produces a complex multi-modal model of TBI that can be useful in laboratory investigation of putative TBI therapies and fundamental neurophysiological processes after brain injury.